2004
DOI: 10.1073/pnas.0402693101
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin-releasing hormone (CRH) requirement inClostridium difficiletoxin A-mediated intestinal inflammation

Abstract: Clostridium difficile, the causative agent of antibiotic-associated colitis, mediates inflammatory diarrhea by releasing toxin A, a potent 308-kDa enterotoxin. Toxin A-induced inflammatory diarrhea involves many steps, including mucosal release of substance P (SP) corticotropin-releasing hormone (CRH) and neutrophil transmigration. Here we demonstrate that, compared with wild type, mice genetically deficient in CRH (Crh ؊/؊ ) have dramatically reduced ileal fluid secretion, epithelial cell damage, and neutroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 49 publications
(65 reference statements)
3
60
0
1
Order By: Relevance
“…In addition, the colonic cell line Caco-2 was used to investigate the cytopathic property of mutant toxins with respect to transepithelial electrical resistance (TER). The TER of confluent Caco-2 cell monolayers grown on filter inserts (Falcon; BD, Germany) was determined, starting with an initial value of at least 150 ⍀ · cm 2 (Fig. 1C).…”
Section: Fig 1 (A)mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the colonic cell line Caco-2 was used to investigate the cytopathic property of mutant toxins with respect to transepithelial electrical resistance (TER). The TER of confluent Caco-2 cell monolayers grown on filter inserts (Falcon; BD, Germany) was determined, starting with an initial value of at least 150 ⍀ · cm 2 (Fig. 1C).…”
Section: Fig 1 (A)mentioning
confidence: 99%
“…Several reports of the in vivo effects of TcdA in animal models reflect efforts to understand the cellular mechanism leading to clinical symptoms as well as to the release of mediators that are involved in the inflammatory process (2,13,15,18,20). The inherent glucosyltransferase…”
mentioning
confidence: 99%
“…Th is is in contrast to a previous study of Liu et al (2006), who reported that in the small intestine of the guinea-pig 55% of CRF-expressing myenteric neurons were also SP-positive and no colocalization of CRF with SP was detected in submucous neurons. It is noteworthy that in the murine ileum, some CRF-IR/SP-IR enteric nerves were found (Anton et al, 2004). In the mammalian intestine SPexpressing myenteric neurons projecting into the circular smooth muscle layer are considered to be cholinergic excitatory motor neurons (Brookes, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Admittedly, Lazar et al (2003) suggested that capsaicin-sensitive neurons do not mediate the eff ect of exogenous CRF in the guinea-pig ileum but other reports have indicated that CRF is an important factor involved in visceral pain development during infl ammatory processes (for a review see Larauche et al, 2009). Since in the wild type mouse, the co-localization of CRF with SP in the ileal enteric nerves is more evident after Clostridium diffi cile toxin A administration it has been proposed that CRF secreted in response to toxin A is correlated with the pro-infl ammatory eff ect of SP (Anton et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…A few studies on the effects of C. difficile toxins on enteric neurons showed that toxin A stimulates extrinsic sensory nerves and causes uncontrolled gut inflammation, likely mediated by substance P from primary afferent neurons [50]; this inflammation was prevented by extrinsic surgical denervation [51,52]. On the other hand, neuronal activation of VIP-positive pathways after exposure to toxin B has been hypothesized as an attempt of a protective adaptive response toward a pathogenic agent aggression of the intestinal mucosa [53].…”
Section: Pi-ibs After C Difficile Infection: a Case Of A Microbiologmentioning
confidence: 99%